Stock Performance Analysis of PT. Kalbe Farma TBK (KLBF) in 2016-2020 - Kukuh Pramandhiko Dipo (CV. Publikasi Indonesia, 2024)
When the World Health Organization (WHO) announced that COVID-19 was upgraded to pandemic status, investors began to reconsider their portfolio structure from risky assets such as stocks to gold. This study aims to determine the stock performance of PT. Kalbe Farma Tbk during the COVID-19 pandemic. A quantitative descriptive approach by linking company financial statement data with the phenomenon of the COVID-19 pandemic is the method used in this study. Based on the results of the research that has been done, it can be concluded that the performance of PT. Kalbe Farma Tbk before and during the COVID-19 pandemic on the dependent variable (stock return), namely the Current ratio, had a significant effect on Stock Return. However, based on the results of hypothesis testing regarding the effect of Earnings Per Share and Net profit margin on Stock Return partially, it can be concluded that these variables do not have a significant effect on Stock Return. Based on the conclusions above, the researcher recommends that the first company is expected to make the value of CR better in order to attract investors in investing their funds. Because if the company has a high CR value then the company can be said to have no constraints to pay its debts, thus many investors will be interested in investing in pharmaceutical sector companies and that can be very profitable for the company. Next is advice for those who want to invest in pharmaceutical companies, it is recommended to look at the CR owned by the company if investors want to make long-term investments.